2013
DOI: 10.1186/1750-1326-8-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional brain mapping in a conditional mouse model of human tauopathy (taup301l) reveals reduced neural activity in memory formation structures

Abstract: BackgroundTauopathies are characterized by intracellular deposition of the microtubule-associated protein tau as filamentous aggregates. The rTg4510 mouse conditionally expresses mutant human tau protein in various forebrain areas under the Tet-off expression system. Mice develop neurofibrillary tangles, with significant neuronal loss and cognitive deficits by 6 months of age. Previous behavioral and biochemical work has linked the expression and aggregates of mutant tau to functional impairments. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
4
38
0
Order By: Relevance
“…Another study by Perez and colleagues observed neuronal dysfunction in the CA3 of five-month-old rTg4510 mice using MEMRI (Perez et al, 2013). Since tau pathology ensues well before five months in rTg4510 mice, it was reasonable to measure changes at earlier time points, which led us to identify MEMRI deficits as early as three months of age in rTg4510 mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Perez and colleagues observed neuronal dysfunction in the CA3 of five-month-old rTg4510 mice using MEMRI (Perez et al, 2013). Since tau pathology ensues well before five months in rTg4510 mice, it was reasonable to measure changes at earlier time points, which led us to identify MEMRI deficits as early as three months of age in rTg4510 mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite such potential limitations, significant attempts have been made, in recent years, to use MEMRI in studies of the pathobiology of neurodegenerative diseases utilizing relevant animal models (Bertrand et al 2013; Perez et al 2013; Drobyshevsky et al 2012; Haenold et al 2012; Morken et al 2013; Saito et al 2012; Wideroe et al 2012; Bouilleret et al 2011; Chan et al 2011; Kim et al 2011; Smith et al 2011; Soria et al 2011; Tang et al 2011; Wideroe et al 2011; Inoue et al 2010; Kawai et al 2010; van Meer et al 2010). Nonetheless and paramount to the successful application of MEMRI is not simply the ability to deliver Mn 2+ to the site of interest or of disease but in determining the cell types and cellular mechanisms that engage the ion and produce the signal enhancement observed.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly assumed that NFT-bearing neurons exhibit deficits in synaptic integration and eventually lead to neurodegeneration (11,12). However, the actual functional properties of NFT-bearing neurons in intact neural circuits have not been explored previously (13).…”
mentioning
confidence: 99%